Genotipagem de HPV proveniente de mulheres soropositivas e soronegativas para HIV atendidas no Centro de Referência em DST/AIDS em Vitória-ES - Mattos, Adriana Tonani de (2010)
Human papillomaviruses (HPV) are epitheliotropic viruses that infect skin tissue or mucous membranes, closely related to development of lesions in the genital tract, ranging from warts to invasive cervical cancer. These injuries are caused by different types of HPV that are classified into low and high risk types according to the association with cervical cancer. HIV seropositive women are mostly affected by HPV and are more prone to develop cervical cancer. The aim of this study was to evaluate the frequency of HPV types in seropositive and seronegative women for HIV. Therefore, cervical samples, part of the human bank samples of the Virology Laboratory, were analised from women known to be positive for HPV (n=87) attending the Reference Center STD / Aids Clinic in Vitória-ES, during March to December 2006. DNA was extracted by commercial kit QIAamp...